Differences in the Quality of Bottom Ash and Fly Ash for the Cement Industry as an Alternative Fuel (AF) - Nurul Faizah Setiaji; Ariyanti Sarwono; I Wayan Koko Suryawan (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
Cement is a prominent Indonesian industry. Industrial fuel needs are growing. In Indonesia, biomass is an essential natural resource with a variety of primary products such as fiber, wood, oil, food, and others that are utilized domestically and exported to generate foreign cash. This study compares fly ash and bottom ash as alternative fuel feedstock materials from the cement industry. This study uses cement industry data from East Java. As, Cd, Cr, Pb, Hg, TI, Sb, Co, Ni, Cu, V, Zn, Se, and Sn for bottom ash and fly ash quality data are employed. The investigation followed a paired t-test to compare ash types based on metal characteristics, then an ANOVA post-test to establish the significance of bottom ash and fly ash values. The paired t-test on two types of ash showed a 0.103 difference. ANOVA shows that ash kinds differ significantly. Bottom ash and fly ash have different qualities. Hence their management requires various approaches. This treatment utilizes bottom ash. For fly ash, the quality-related parameters must be lowered.